LncRNA MIAT downregulates IL-1β, TNF-ɑ to suppress macrophage inflammation but is suppressed by ATP-induced NLRP3 inflammasome activation - Wang, Ziye (Cell Cycle, 2021)
Cardiovascular disease (CVD) has been identified as the leading cause of premature deaths in rheumatoid arthritis (RA), accounting for about 40 to 50% of all deaths. Macrophage inflammation is regarded as a key point to link to the two diseases. Recently, long non-coding RNAs (lncRNAs) have acknowledged as a regulator of inflammation significantly. Here, we firstly found that lncRNA myocardial infarction associated transcript (lncRNA MIAT), a crucial lncRNA to regulate CVD, expressed increasingly in synovium and myocardial tissues of collagen-induced arthritis (CIA) mice. Besides, we also verified that the increased infiltration of macrophage occurred in those tissues of the CIA. In vitro, we found that macrophage inflammation induced by LPS could up-regulate lncRNA MIAT expression. LncRNA MIAT seemed to inhibit the expression of IL-1β, TNF-ɑ and be suppressed by ATP-induced NLRP3 inflammasome activation pathway. Therefore, these data indicated an anti-inflammatory effect of lncRNA MIAT in macrophage and an original research direction for high cardiovascular risk in RA.